2014
DOI: 10.1007/s12272-014-0344-2
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin-3-O-β-d-glucuronide isolated from Polygonum aviculare inhibits cellular senescence in human primary cells

Abstract: Cellular senescence is known to contribute to tissue aging, a variety of age-related diseases, tissue regeneration, and cancer. Therefore, aging intervention might be useful for prevention of aging as well as age-related disease. In this study, we investigated compounds from Polygonum aviculare to determine if they inhibited cellular senescence in human primary cells, human dermal fibroblasts (HDFs) and human umbilical vein endothelial cells (HUVECs). Ten compounds from P. aviculare were purified and their inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 46 publications
1
17
0
Order By: Relevance
“…contribute to the variations in the anticancer properties of the extracts. Previous studies revealed the anticancer effects of quercetin glucosides in in vitro studies (15,20,21). The present results indicate that quercetin glucosides are potent in HepG2, HT-29 and PC-3 cancer cell lines.…”
Section: Activities Of Individual Quercetin Glucosides Allium Cepa Lsupporting
confidence: 66%
See 3 more Smart Citations
“…contribute to the variations in the anticancer properties of the extracts. Previous studies revealed the anticancer effects of quercetin glucosides in in vitro studies (15,20,21). The present results indicate that quercetin glucosides are potent in HepG2, HT-29 and PC-3 cancer cell lines.…”
Section: Activities Of Individual Quercetin Glucosides Allium Cepa Lsupporting
confidence: 66%
“…The major extractable quercetin glucosides in the Allium cepa L. were 3,4'-Qdg and 4'-Qmg, and 3'-Qmg was also detected in this species. The composition analysis of Allium cepa L is presented in Table I, which indicates that 3,4'-Qdg is the major phenolic compound present in onions (20,21). Certain quercetin glucosides may be cross-linked to cell-wall polysaccharides in the form of dimers that may be attributed to the quercetin glucosides level in the fraction obtained from different genus Allium (20,21).…”
Section: Activities Of Individual Quercetin Glucosides Allium Cepa Lmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, it has been reported that avicularin, quercetin-3-α-L-arabinofuranoside, exerts antioxidant and anti-inflammatory activity (Vo et al ., 2012). Quercetin-3- O - β -D-glucuronide (QG) has been reported to anti-cancer (Yamazaki et al ., 2014), anti-aging (Yang et al ., 2014), and anti-oxidant properties (Messer et al ., 2015). However, the underlying mechanism by which QG exerts its pharmacological activity has not been clearly demonstrated.…”
Section: Introductionmentioning
confidence: 99%